Implementasi Metode Timeline pada Materi Sejarah Kebudayaan Islam dalam Pembelajaran PAI di SMA Negeri 2 Padang - Nisa, Khairatun (Lembaga Yasin AlSys, 2023)
This research is motivated by an understanding of the importance of using methods in learning, and adapting methods to the material presented. This study aims (1) to describe the planning of the timeline method on Islamic Cultural History material in PAI learning at SMA Negeri 2 Padang. (2) to describe how the timeline method is implemented in Islamic Cultural History material in Islamic Religious Education learning at SMA Negeri 2 Padang. (3) to describe how to evaluate the timeline method on Islamic Culture History material in PAI learning at SMA Negeri 2 Padang. (4) to determine the inhibiting and supporting factors for the implementation of the timeline method on Islamic Cultural History material at SMA Negeri 2 Padang. This research uses descriptive qualitative method. The objects of this study were students and teachers of Islamic Religious Education at SMA Negeri 2 Padang. The subject of this research is student learning outcomes, then data obtained from observations, interviews, with informants and documentation. The results of this study indicate that first, planning the timeline method on the material History of Islamic Culture in Padang 2 Public High School first the teacher must prepare teaching modules, which contain all the teacher's needs when teaching such as: learning outcomes, learning flow and objectives, learning methods, learning media, steps in learning, forms of assessment in learning, learning resources and materials. Second, the implementation of learning using the timeline method consists of three stages, namely opening, core and closing. Third, the evaluation of the timeline method is carried out in two ways, namely the oral and written methods. Or grouped into two formative assessments and summative assessments. Fourth, the inhibiting and supporting factors, the major inhibiting factors are the students' own learning styles and some students are less active during discussions, supporting methods are easy to understand, simple, the resources students need are already in school, the media needed is easy to obtain. The based on the research conducted in can be understood that in the implementation of the timeline method the are arethings that must be prepared including, planning which contains teaching modules tahar contain all the needs when teaching, the implementation, in the implementation section consists of three stages namely opening, core, closing, then the next stage evaluaction, ehich is related to assessment, found that can be done, namely through oral tests and writtwn twest, while the inhibiting factors lie in the different stundent learning styles, supporting factor such as the method are simple, the media needed is easy to obtain, the resouces needed are al ready evailaable by the scholl.